1978
DOI: 10.1007/bf01915321
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological oxidation of the pentyl side chain of cannabinoids

Abstract: Syncephalastrum racemosum ATCC 18192 and Mycobacterium rhodochrous ATCC 19067 partially degrade the n-pentyl side chain of cannabidiol, cannabinol, delta8-tetrahydrocannabinol and delta9-tetrahydrocannabinol. Carboxylic acid and alcohol side chain derivatives are major metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…It is unclear why total THCCOOH concentrations were unstable, although altered adsorption, intramolecular acyl migration, protein binding, or further molecular degradation could explain these changes. Early synthesis of cannabinoid metabolites used microbial transformation to produce certain metabolites on the pentyl side chain [28]. Skopp et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why total THCCOOH concentrations were unstable, although altered adsorption, intramolecular acyl migration, protein binding, or further molecular degradation could explain these changes. Early synthesis of cannabinoid metabolites used microbial transformation to produce certain metabolites on the pentyl side chain [28]. Skopp et al .…”
Section: Discussionmentioning
confidence: 99%
“…Biotransformation of cannabinoids to glucosylated forms by plant tissues (Tanaka et al 1997) and various oxidized derivatives by microorganisms (Robertson et al 1978;Binder and Popp 1980) have been reported; as well as biotransformations for olivetol (McClanahan and Robertson 1984). However, the best studied biotransformations are in animals and humans (Mechoulam 1970;Watanabe et al 2007).…”
Section: Cannabinoid Biosynthesismentioning
confidence: 96%
“… 113 Ring- and side-chain hydroxylated derivatives, namely 3′′-OH-CBD,4′′,5′′-dinor, 4′′-OH-CBD, 4′′,6α-diOH-CBD, and 3′′,6-diOH-CBD,4′′,5′′-dinor, have also been produced in milligram quantities by microbial oxidation. 114 The synthesis of the 7-COOH metabolite of CBD has been described. 74 , 115 Synthesis of the side-chain terminal carboxylic acid (5′′-COOH, identified only in animals 116–119 ) has also been described.…”
Section: Synthesis Of Cbd Metabolitesmentioning
confidence: 99%